Pembentukan Dimensi Bergotong Royong dalam Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di Sekolah Penggerak SMA Darut Taqwa Purwosari Pasuruan - Ratu Nata, Balqisa; Muhibin Zuhri, Achmad; Rubaidi; Ilma Silfiah, Rossa (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
This research aims to examine several problems including actualization of the formation of mutual cooperation dimensions in Learning Islamic Religious Education and Character at the Darut Taqwa High School Driving School, Purwosari Pasuruan and analysis of the results of the formation of the mutual cooperation dimension in Learning Islamic Religious Education and Character at the Darut Taqwa Purwosari Pasuruan Driving School. This research is included in the type of field research using a qualitative descriptive approach. This research shows the results that (1) The actualization of the formation of the mutual cooperation dimension in learning Islamic Religious Education and Character at the Darut Taqwa High School Driving School, Purwosari Pasuruan, can be divided into three elements. First, the collaboration element is learning using cooperative learning models and positive habituation learning activities. Second, the element of care is concern in the process of completing group assignments, community service project activities, extracurricular activities, peer tutoring activities, cleaning classes and the school environment. Third, the sharing element is sharing knowledge by having the same answer in cooperative learning, social fund contributions for those in need, and sharing food after being visited by their parents. (2) The results of the formation of the dimension of mutual cooperation in learning Islamic Religious Education and Character at the Darut Taqwa High School Driving School, Purwosari Pasuruan is being able to develop character, being able to improve social skills, and having an attitude of solidarity and unity.